First report of Tomato chlorosis virus on tomato crops in Cyprus - Papayiannis, Lambros C.; Dovas, Chrysostomos I.; Maliogka, Varvara I.; Katis, Nikolaos I.; Ioannou, Nicolas (My University, 2006)
In the summer of 2004, yellowing symptoms similar to those caused by nitrogen and/or magnesium deficiency were observed in field- and glasshouse-grown tomatoes ( Lycopersicon esculentum ), in the Parekklisia area of Cyprus. Initially, lower leaves showed extensive interveinal yellowing with necrotic flecks, brittleness and occasional upward leaf rolling, before finally the whole plant turned yellow. Similar symptoms were observed during 2005 in glasshouse tomatoes grown in areas located on the southwest coastal region of the island. The abundance of whiteflies on the affected plants suggested the involvement of the whitefly-transmitted Tomato chlorosis virus (ToCV) and/or Tomato infectious chlorosis virus (TICV), both of the genus Crinivirus (Wisler et al ., 1998). Leaves of 18 affected plants were collected, total RNA was isolated and RT-PCR was performed in a single tube using primers HS-11 and HS-12, followed by a multiplex nested-PCR with primers TIC-3/TIC-4 and ToC- 5/ToC-6, for the detection of TICV and ToCV, respectively (Dovas et al ., 2002). A PCR product of 463 bp, corresponding to the HSP 70 gene of ToCV, was amplified for all tested samples. The sequences of four cloned PCR products were identical (EMBL accession number AM158958) and showed 99% nucleotide identity to a ToCV isolate from Florida (accession number AY903448). ToCV is vectored by Bemisia tabaci ( biotypes A and B ), Trialeurodes vaporariorum and T. abutilonea . Although there have been no systematic studies on whitefly incidence and distribution in Cyprus, it seems that B. tabaci is the predominant species present, as Tomato yellow leaf curl virus (Ioannou, 1985) and Cucurbit yellow stunting disorder virus (Papayiannis et al ., 2005), vectored by this species, are prevalent in tomatoes and cucurbit crops, respectively. On the other hand, the incidence of Beet pseudo-yellows virus (transmitted by T. vaporariorum) is much lower. This is the first report of ToCV in Cyprus.
Keywords: Fruit; Viral disease